Analisis Perlakuan Akuntansi Pajak Pertambahan Nilai Pada PT Hasjrat Abadi Cabang Manado - Ma'Arif, Patrick; Wangarry, Andreas Randy; Pangemanan, Shane A.; Tangon, Joseph N. (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
PT Hasjrat Abadi Manado Branch is a private company in Manado, and operates in the general trading sector. PT Hasjrat Abadi Manado Branch opened a branch in the city of Manado to serve the needs of the community, especially four-wheeled vehicles with the "TOYOTA" brand. The aim of the research is to determine the accounting treatment for Value Added Tax (VAT) at PT. Hasjrat Abadi Manado Branch in accordance with Law Number 7 of 2021. The research method used is a qualitative method, this method is considered relevant because it focuses on uncovering a phenomenon regarding the object under study. The data collection techniques used were interviews, observation and documentation. For the data sources used, primary data is a type of data collected directly from the main source. This research examines the treatment of Value Added Tax (VAT) at PT Hasjrat Abadi Manado Branch through the implementation of the Self Assessment System. This system gives taxpayers the authority to independently calculate, deposit and report the tax owed, which requires high accuracy and compliance. This study explains the mechanism for recording Input VAT and Output VAT, as well as the steps for reporting and remitting VAT that have been carried out by companies. The analysis shows that accurate and timely recording is critical to minimizing the risk of sanctions from tax authorities and ensuring compliance with applicable regulations. Apart from that, this research also identifies the challenges faced by companies in implementing the Self Assessment System, such as the need for an in-depth understanding of tax regulations and potential audit risks. However, this system also provides flexibility and efficiency in managing corporate taxes. The results of this research emphasize the importance of a strong accounting system and adequate knowledge about taxation to support the effective implementation of the Self Assessment System in companies.